Determinants of poverty among coastal fisherman crews in Kelantan and Terengganu, Malaysia - Rhoumah, Ali Mohamed Omar (2017)
The poverty issue has become one of the most challenges problem is facing the United Nation since 1978 when planned to reduce extreme poverty around the world. The number of people who left extreme poverty line is increasing for example, in China about 200-300 million have lifted an extreme poverty during the period 1978-2000s. Furthermore, the worldwide poverty was reduced from 900 million in 2012 to about 700 million in 2015 (Millennium Development Goals). However, there are hundreds of millions of children still out of schools and do not have access to basic needs such as health care, electricity, and clean water. The majority of poor people is located in Sub-Saharan Africa and south Asian countries such as Pakistan, Myanmar and Vietnam.